2021
DOI: 10.3390/ijms22031079
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel lncRNAs in Ovarian Cancer and Their Impact on Overall Survival

Abstract: Long non-coding RNA’s (lncRNA) are RNA sequences that do not encode proteins and are greater than 200 nucleotides in length. They regulate complex cellular mechanisms and have been associated with prognosis in various types of cancer. We aimed to identify lncRNA sequences that are associated with high grade serous ovarian cancer (HGSC) and assess their impact on overall survival. RNA was extracted from 112 HGSC patients and 12 normal fallopian tube samples from our Biobank tissue repository. RNA was sequenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…Gene CNV was estimated using SAMtools and superFreq [ 34 ]. BAM files were then used to identify lncRNA, as described previously [ 35 , 36 ]. Lastly, fusion transcripts were determined using the STAR-Fusion suite from fastq files [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gene CNV was estimated using SAMtools and superFreq [ 34 ]. BAM files were then used to identify lncRNA, as described previously [ 35 , 36 ]. Lastly, fusion transcripts were determined using the STAR-Fusion suite from fastq files [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…What is most noteworthy is that many studies have shown that there is a close relationship between the differential expression of miRNA and tumor, which provides a new idea for us to treat tumor. lncRNA is a non-coding RNA with a length of more than 200 nucleotides 16 . Previous studies have shown that it is involved in many important regulatory processes, such as X chromosome silencing, genomic imprinting, chromatin modi cation, transcriptional activation, transcriptional interference, and intranuclear transport 17 .…”
Section: Discussionmentioning
confidence: 99%
“…TCGA-OV cohort composed of 373 samples with expression profiles was used to identify prognostic DEGs. In addition, a cisplatin response model was developed based on TCGA-OV dataset that included 209 complete response and 27 progressed disease samples after chemotherapy, which was validated in the GSE156699 dataset consisting of 38 cisplatin nonresponse patients and 50 response patients [ 29 ]. Possible associations of the model with other cisplatin resistance pathways as well as immune checkpoint genes were also investigated in TCGA-OV dataset.…”
Section: Methodsmentioning
confidence: 99%